(3TQM eG hbY aj cJGH (B" (3GdLhGgQ GdMSGf aj JaSjQ GdbQBf ef GdCdaGX GdZjHIs - (3CHh RjO YHO GdQMef Hf eMeO Hf eNdha GdKYGdHi GdLRGFQis; (3CHhRjO GdKYGdHj , CHh RjO,J (B875 (3g` s
(3ChdgG (B:s
(3CeG HYO Efg deG jSQ Gddg Ydi EceGd gPG GdeNJUQ haQZJ ef JUMjMg , hcKjQ GdQGZHhf ai JMUjdg SCdJi HYV ENhGfi Cf CdMb Hg TQM eG hbY ajg ef GdbQjH djJe HPdc ebUhO GdcJGH aCNHJge Edi Pdc s
(3BNQgG (B:s
(3ef HGH MQa GdjGA , bhdg (B: (3bGd GdLhgQi (B: (3CQV jHGH Ci NQGH hPgHhG CjGOi JaQbhG hai GdMOjK (B: (3cd ejSQ deG Ndb dg , Ci egjC heUQha Edjg GfJgi HMeO Gddg s
(3HgG fXGe GdJYbjHIs
(3hai HYV ChQGbgG JQbjY hWeSs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B331 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B192s
Keywords: (3GddZIs